Mechanical energy fluctuations and propulsion in double poling - Danielsen, J.; Sandbakk, O.; Holmberg, H. C.; Ettema, G. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: The study of the mechanical energy (ME) fluctuations of the center of mass and/or body has recently been applied to cross-country (XC) skiing techniques (1,2). Pellegrini et. al. (2) argued that double poling (DP) is similar to that of the inverted pendulum mechanism as seen in walking, where the kinetic (Ekin) and gravitational potential (Epot) energies fluctuates out-ofphase. The present study investigated these energy fluctuations in DP and included instantaneous measurements of external work (Wext) generation. We, in contradiction with Pellegrini et al. (2), hypothesized that Ekin and Epot would fluctuate more in-phase, and that Ekin+pot (i.e. total ME) would show large fluctuations over the movement cycle, increasing in retrieval and decreasing in the poling phase. In that way, body ME can directly be transferred to do Wext as the main mechanism of propulsion in DP.